Integrated Weed Management in Kharif Direct Seeded Rice (Oryza sativa L.) in Medium Black Soil of Konkan Region of Maharashtra - Dademal, A. A.; Jagtap, D. N.; More, V. G.; Bodake, P. S.; Mhaskar, N. V.; Pinjari, S. S.; Dahiphale , A. V. (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was conducted at ARS, Repoli, Maharashtra, India during kharif (June to October) seasons of 2019, 2020 and 2021 to study integrated weed management in direct seeded rice (Oryza sativa L.). The experiment was replicated in randomized block design with seven treatments viz., T1: Oxadiargyl 80% WP (PE) @ 100 g ha-1, T2: Oxadiargyl 80% WP (PE) @ 100 g ha-1 fb HW at 30 DAS, T3: Oxadiargyl 80% WP (PE) fb Bispyribac-Na @ 25 g ha-1 at 25 DAS, T4: Oxadiargyl 80% WP (PE) fb Metasulfuron-methyl+chlorimuron-ethyl @ 4 g ha-1 at 25 DAS, T5: Oxadiargyl 80% WP (PE) fb carpentrozone ethyl 40% @ 25 g ha-1 at 25 DAS, T6: Weed free check (2HW at 20 and 40 DAS) and T7: Unweeded check (control). Based on pooled analysis, Significantly least number of weeds and dry weight of grasses, sedges and broad leaves weeds and higher yield attributes and yield were recorded in weed free check (2HW at 20 and 40 DAS) followed by Oxadiargyl 80% WP as Pre-emergence (PE) @ 100 g ha-1 fb HW at 30 DAS and Oxadiargyl 80% WP (PE) fb Metasulfuron-methyl+chlorimuron-ethyl @ 4 g ha-1 at 25 DAS treatments. The highest weed control efficiency, net returns with benefit-cost ratio was also obtained in the weed free check followed by by Oxadiargyl 80% WP as Pre-emergence (PE) @ 100 g ha-1 fb HW at 30 DAS and Oxadiargyl 80% WP (PE) fb Metasulfuron-methyl+chlorimuron-ethyl @ 4 g ha-1 at 25 DAS treatments. Among sequential herbicide treatments, application of Oxadiargyl 80% WP (PE) fb Metasulfuron-methyl+chlorimuron-ethyl @ 4 g ha-1 at 25 DAS (T4) recorded least number of weeds m2 (5.82, 6.12 and 9.04) and dry weight m2 (2.08, 2.50 and 4.08 g m-2) as compared to other sequential herbicide treatments. Similarly highest weed control efficiency that is 72.97, 80.37 and 70.46% at 40, 60 DAS and at harvest stage, respectively recorded in treatment T4. Similarly the yield attributing characters and grain and straw yield (4859 and 4816 kg ha-1) was recorded highest in treatment T4.